HEALTH EDUCATION AND PRIVATE VOC HEALTH EDUCATION AND PRIVATE VOCATIONAL SCHOOL TRAINING "CARE FOR PUBLIC WOMEN REMAINING HEALTHY IN THE PANDEMIC TIME COVID 19" - S.ST., M.KEB, SUMARNI; Annisa, Rosmina; Yuliana, Yuliana (PITIMAS: Journal of Community Engagement in Health, 2023)
Abstract Uterine involution is a change which is the process of returning the uterus or uterus and birth canal after the baby is born until it reaches a pre-pregnancy state that is influenced by mobilization and childbirth exercises. During the postpartum period, mothers are required to do postpartum gymnastics or exercises after childbirth. This gymnastics is carried out from the first day after giving birth to the tenth day. In 2015, almost 68% of postpartum mothers never did postpartum exercise. This community service takes the form of 2 activities, namely health education and postpartum gymnastics training. The health education methods used were lectures and questions and answers. Meanwhile, postpartum gymnastics training includes the correct role model of postpartum gymnastics techniques. The purpose of this Community Service is to restore postpartum fitness. Participants of health education and postpartum gymnastics training were 20 postpartum mothers. Community service activities were carried out for 1 day in the Hall of the Tahirah Al Baeti Midwifery Academy in Bulukumba. After participating in this activity, the participants understood and were able to independently practice puerperal gymnastics. This community service is expected to provide knowledge and skills to postpartum mothers about postpartum exercise, so that respondents have the independence to do postpartum exercise. Keyword : gymnastics, puerperium, involution